24. Dorsal column nuclei evoked activity recorded from the human Pedunculopontine nucleus. Issue 12 (December 2016) - Valeriani, M.; Insola, A.; Mazzone, P.
Abstract : This study aimed to verify the hypothesis that somatosensory activity recorded from the Pedunculopontine nucleus (PPTg) comes from the dorsal column nuclei (DCN) (Insola et al., 2015). In one parkinsonian patient implanted in the PPTg for DBS, both tibial and median nerve SEPs were recorded from the PPTg electrode. The finding obtained from this patient was compared with that issued from another patient implanted with an epidural electrode at Cv2 level for pain relief. The triphasic waform and HFOs recorded from the PPTg after tibial nerve stimulation were very similar to the low- and high-frequency components recorded from the Cv2 epidural electrode, known to be generated in the DCN (Insola et al., 2010). Therefore, the present results suggest that both the low-frequency triphasic waveform and the HFOs recorded from the PPTg are generated from the DCN.